Criação musical coletiva com crianças: possíveis contribuições para processos de educação humanizadora - Silva, Mariana Galon da (Universidade Federal de São Carlos, 2015)
This dissertation sought to investigate the applicants educational processes of social practice of collective musical creation. Through the research presented here aimed to analyze the educational processes generated from 5 collective musical creation activities for boys and girls in social project Tocando à Vida , from Ribeirão Preto, in order to identify whether these processes contribute to the formation these human male and female students. The collective musical creation activities such as social practices, understand that favor togetherness guided dialogue and collaboration, thereby, we seek to understand how these activities can contribute to humanizing music education. For research we propose to carry out the methodology of participatory research where data collection started from an insert within that space was adopted so that observations of these educational processes happen in contact with students and students during the performance of music creation activities collective. The Project Playing to Life, Ribeirão Preto SP provides free group lessons of musical instruments for children 06-13 years. The inserts in order to collect data occurred in the course of eight months, which participated in the activities of collective musical creation proposals 10 male and female students. The data collections were made by observing the activities, and wheels of talks held after the activities. As memory resources records in field diary and recording the wheels of conversations and musical creations of the students were used. The authors that guided the analysis were Paulo Freire, Ernani Maria Fiori, Enrique Dussel, Carlos Rodrigues Brandão, Hans -Joachim Koellreutter , Maria Teresa Alencar de Brito, Jorge Larrosa Bondia, among others. As a result it was possible to observe the changes in the relations between male and female students, with regard to the development of guided dialogue in loveliness, conquest of autonomy and the search for the humanization. The analysis of the educational processes that are generated social practice occurring during collective musical creation activities within the Project Tocando à Vida can contribute to change of view on this kind of activity, generating a favoring of human formation of children who learn music.
Keywords: Educação musical; Criação musical coletiva; Processo educativo; Humanização; Criança; Convivência; Collective musical creation; Educational processes; Humanization; Children; Coexistence; CIENCIAS HUMANAS::EDUCACAO